Calculation of electricity sales based on multi-factor correlation analysis - Zhou, Jian; Tuo, Jianjun; Wang, Lingbo; Shi, Yaqi; Zha, Wenting (Frontiers in Energy Research, 2023)
Electricity sales is one of the important assessment indexes of a power grid company’s operation. Since electricity sales is closely related to many factors, how to consider the influence of multiple factors and improve the accuracy of the calculation of electricity sales is a difficult problem that needs to be solved urgently. In this paper, we first analyze the six dimensions affecting electricity sales and select the key influencing factors that can be quantified statistically. Secondly, the key influencing factors are screened according to Pearson’s correlation coefficient and then the calculation model of electricity sales is established based on the random forest algorithm. Finally, we validate the feasibility and validity of the proposed calculation method for electricity sales through a case study.